SBRT of ventricular tachycardia using 4pi optimized trajectories. Issue 12 (22nd October 2021) - Q. M. Reis, Cristiano; Little, Brian; Lee MacDonald, Robert; Syme, Alasdair; Thomas, Christopher G.; Robar, James L.
Abstract: Purpose: To investigate the possible advantages of using 4pi‐optimized arc trajectories in stereotactic body radiation therapy of ventricular tachycardia (VT‐SBRT) to minimize exposure of healthy tissues. Methods and materials: Thorax computed tomography (CT) data for 15 patients were used for contouring organs at risk (OARs) and defining realistic planning target volumes (PTVs). A conventional trajectory plan, defined as two full coplanar arcs was compared to an optimized‐trajectory plan provided by a 4pi algorithm that penalizes geometric overlap of PTV and OARs in the beam's‐eye‐view. A single fraction of 25 Gy was prescribed to the PTV in both plans and a comparison of dose sparing to OARs was performed based on comparisons of maximum, mean, and median dose. Results: A significant average reduction in maximum dose was observed for esophagus (18%), spinal cord (26%), and trachea (22%) when using 4pi‐optimized trajectories. Mean doses were also found to decrease for esophagus (19%), spinal cord (33%), skin (18%), liver (59%), lungs (19%), trachea (43%), aorta (11%), inferior vena cava (25%), superior vena cava (33%), and pulmonary trunk (26%). A median dose reduction was observed for esophagus (40%), spinal cord (48%), skin (36%), liver (72%), lungs (41%), stomach (45%), trachea (53%), aorta (45%), superior vena cava (38%), pulmonary veins (32%), and pulmonary trunk (39%). No significant difference was observed for maximum dose ( p = 0.650) and homogeneity index ( p = 0.156) for the PTV. Average values of conformity number were 0.86 ± 0.05 and 0.77 ± 0.09 for the conventional and 4pi optimized plans respectively. Conclusions: 4pi optimized trajectories provided significant reduction to mean and median doses to cardiac structures close to the target but did not decrease maximum dose. Significant improvement in maximum, mean and median doses for noncardiac OARs makes 4pi optimized trajectories a suitable delivery technique for treating VT.